Teachers Voices Interpreting Standards - Rigsby, Leo C.; DeMulder, Elizabeth K. (Education Policy Analysis Archives, 2003)
The State of Virginia has adopted state-mandated testing that aims to raise the standards of performance for children in our schools in a manner that assigns accountability to schools and to teachers. In this paper we argue that the conditions under which the standards were created and the testing implemented undermine the professionalism of teachers. We believe this result has the further consequence of compromising the critical thinking and learning processes of children. We argue this has happened because teachers’ views and experiences have driven neither the setting of standards nor the assessment of their achievement. We use data from essays by teachers in an innovative masters program to compare teachers’ experiences involving the Virginia Standards of Learning with ideal standards for professional development adopted by the National Board for Professional Teaching Standards. We argue that there are serious negative consequences of the failure to include dialogue with K-12 teachers in setting standards and especially in the creation of assessments to measure performances relative to the standards. We believe the most successful, honest, and morally defensible processes must be built on the experience and wisdom of classroom teachers.